Pengaruh Beban Pajak Tangguhan, Beban Pajak Kini dan Perencanaan Pajak dalam Mendeteksi Manajemen Laba - Aulia Rahmi; Amir Hasan; Andreas Andreas (Jurnal Ekonomi, 2019)
This study aimed to determine the influence of deferred tax expense, current tax, and tax planning on earnings management. Independent variables used in this study are deferred tax expense, current tax, and tax planning while the dependent variable in this study is earnings management are measured using discretionary accrual (DA). Populations used in this study is manufacture sector industries and consumption companies listed on IDX 2012- 2016, where the total sample used is 34 companies. The sampling technique used was purposive sampling technique in which the number of observations obtained this study was 170 (34x5). Data analysis conducted with Binary logistic regression model with help of software SPSS version 20,0. Of the result of the testing that has been done, the wall test showed that the independent variables tax planning which has a significant influence on earnings management, while the deferred tax expense and current tax variables did not significantly affect the earnings management.